PERANCANGAN SISTEM INFORMASI REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH ACEH SINGKIL - Linda Handayani (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Patient medical record information system at the Aceh Singkil Local General Hospital was a system that aimed to manage the patient’s data that registered for treatment until the patient leaved the hospital at a certain period. In this case, information system was so important to be designed for preventing from the errors in the implementation of the registration procedures and data processing in order to use it as well as possible. Administration of medical records of patients at the Aceh Singkil Local General Hospital was still manual so that the patient service become slow and patient medical records were often lost or not found. Designing of patient medical record information system aimed to design the patient medical record information systems based on Visual Basic in order to ease the registration process and to make recapitulation reports of patient visits. In designing of patient medical record information systems at the Aceh Singkil Local General Hospital was using System Development Life Cycle method or system development life cycle that consists of system planning, system analysis, system design conceptually, the evaluation of the system selection, a functional system design, and system implementation.The design of this system produces an application of the patient registration until the patient leave the hospital consists of three forms, namely monthly summary report visit of inpatients and outpatients, and summary annual reports of the highest diseases.The design of patient medical record information systems at Aceh Singkil Local General Hospital was expected to ease patient registration process and to make a report at the hospital so that the hospital can produce accurate data.